Efektifitas Bahan Ajar "Buku Panduan Pembelajaran Kebencanaan Banjir Kabupaten Klaten" Dengan Menggunakan Strategi Think Pair Share Terhadap Hasil Belajar Siswa Di SMK Negeri 1 Klaten - Rizka, Atikah; , Dra. Siti Taurat Aly, M.Pd (2016)
Klaten regency has potential natural disaster one of the disasters that might occur in the district of Klaten is flooding. This study aimed to describe the effectiveness of teaching materials on disaster learning guide books Klaten district, which in this case the researchers used a strategy of "Think Pair Share" in the delivery of the material. The use of learning strategies using the "Think Pair Share" is expected to help students in accepting the delivery of learning material flood disaster. This research was conducted at SMK Negeri 1 Klaten at Jl. Wahidin Sudiro Husodo No. 22 in the village of Klaten coincide Sekarsuli RT: 02/05, village Sekarsuli Northern District of Klaten regency, Central Java. This type of research is selected experimental research, while the design of the study using Nonequivalent Control Group Design. The method used in the study was the experimental class and control class. Experimental classes performed on class SSB many as 17 students in this class uses a strategy Think Pair Share, whereas the control class performed on X Accounting 2 at 29 using a conventional strategy (lectures). Data collection was performed by delivering a matter of pre-tests and post-tests were performed on experimental class or grade control. This study uses a paired sample t-test, in order to see whether there is a difference in treatment between pre-test and post-test on each strategy. Based on the results of the average value of both classes of experiments using strategies Think Pair Share values obtained pre-test post-test 81.26 and 89.29, from the value increased by 8.03%. The average value of the control class from pre-test to post-test 74.9 87.45 increased by 12.55%, so it can be concluded that both the carrying out of the strategy to increase learning outcomes, the highest value obtained from the post-test Think Pair Share strategies. Improved learning results indicate that there is the effectiveness of teaching materials on disaster learning guide books Klaten district mainly by using Think Pair Share strategies for increasing the value of the average post-test was higher than using a conventional strategy (lectures).